1 - China in West Africa’s Regional Development and Security Plans - Akyeampong, Emmanuel (Africa Development, 2021)
This article argues that we are presently in another global economic transition. The old centres of growth have witnessed serious economic reverses with several countries going into ‘receivership’ in the West – Greece, Cyprus, Portugal, Northern Ireland, and possibly Spain and Italy. The fastest growing economies in the world are no longer in the West but in developing regions such as Africa and Asia. China has emerged overnight as the second largest economy with predictions that it would overtake the United States within the next generation. China’s economy has gone from one of export-driven growth to the prospect of continued growth based on internal demand, driven by one of the fastest and largest growing middle classes in history. South–South trade also holds great promise as one of the engines of continued growth for China. China’s recent rise began with its designation as the world’s ‘factory’ by Western multinational companies in the 1980s, seeking to increase their profit margins by outsourcing production to areas with cheap but disciplined labour. As China moves beyond the initial phase of labour-intensive industries to more technologically advanced industries, it has turned to developing countries in continents such as Africa for raw materials, investment and business opportunities in areas such as the construction of infrastructure (roads, railways, hydroelectric dams and so on).